The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1687814020962351
|View full text |Cite
|
Sign up to set email alerts
|

Performance and emission characteristics of a diesel engine employing straight vegetable oils from Vanuatu as fuels

Abstract: The performance characteristics of the engine and the emission levels with Copra Oil (CPO), Virgin Coconut (cocos nucifera) Oil (VCO), Tamanu (calaphyllum inopyllum) Oil (TMO), and Nangae (canarium indicum) Oil (NGO) are presented. The oils, obtained from naturally grown trees in Vanuatu, were tested as straight vegetable oils (SVOs) in a Diesel engine and the results are compared with those of neat diesel. The oils were converted to their fatty-acid-methyl-esters (FAMEs) using gas chromatography to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Although, comparable NOx, higher CO and HC emissions were observed for SVO than FD at all loads. Sisi et al 91 conducted experiments on 3C, 4S, WC, and DE using pure SVO fuels, and insignificant variations in BSFC for SVOs were found without engine knocking. They reported that the BTE of SVOs was established to be analogous with FD at 75% load.…”
Section: Effect Of Svos On Engine Performance and Emission At Varying...mentioning
confidence: 99%
“…Although, comparable NOx, higher CO and HC emissions were observed for SVO than FD at all loads. Sisi et al 91 conducted experiments on 3C, 4S, WC, and DE using pure SVO fuels, and insignificant variations in BSFC for SVOs were found without engine knocking. They reported that the BTE of SVOs was established to be analogous with FD at 75% load.…”
Section: Effect Of Svos On Engine Performance and Emission At Varying...mentioning
confidence: 99%
“…When Sisi et al [62] tested a 3-cylinder, 4S, diesel engine running on tidy SVO; they noticed no changes in BSFC. They also added that the BTE of neat SVO was time-honored to be equivalent with DF at 3/4th engine load.…”
mentioning
confidence: 99%